Disparities in cancer genetics care by race/ethnicity among pan‐cancer patients with pathogenic germline variants. Issue 21 (30th August 2022) - Liu, Ying L.; Maio, Anna; Kemel, Yelena; Salo‐Mullen, Erin E.; Sheehan, Margaret; Tejada, Prince Ray; Trottier, Magan; Arnold, Angela G.; Fleischut, Megan Harlan; Latham, Alicia; Carlo, Maria I.; Murciano‐Goroff, Yonina R.; et al.
Abstract : Background: Germline risk assessment is increasing as part of cancer care; however, disparities in subsequent genetic counseling are unknown. Methods: Pan‐cancer patients were prospectively consented to tumor‐normal sequencing via custom next generation sequencing panel (Memorial Sloan Kettering‐Integrated Mutation Profiling of Actionable Cancer Targets) inclusive of germline analysis of ≥76 genes from January 2015 through December 2019 (97.5% research nonbillable) with protocol for genetics referral. Rates of pathogenic/likely pathogenic germline variants (PVs) and downstream counseling were compared across ancestry groups (mutually exclusive groups based on self‐reported race/ethnicity and Ashkenazi Jewish [AJ] heritage) using nonparametric tests and multivariable logistic regression models. Results: Among 15, 775 patients (59.6%, non‐Hispanic [NH]‐White; 15.7%, AJ; 20.5%, non‐White [6.9%, Asian; 6.8%, Black/African American (AA); 6.7%, Hispanic; 0.1%, Other], and 4.2%, unknown), 2663 (17%) had a PV. Non‐White patients had a lower PV rate ( n  = 433, 13.4%) compared to NH‐Whites ( n  = 1451, 15.4%) and AJ patients ( n  = 683, 27.6%), p  < .01, with differences in mostly moderate and low/recessive/uncertain penetrance variants . Among 2239 patients with new PV, 1652 (73.8%) completed recommended genetic counseling. Non‐White patients had lower rates of genetic counseling (67.7%) than NH‐White (73.7%) and AJ patients (78.8%), p  < .01, with lower rates occurring in Black/AA (63%) compared to NH‐White patients, even after adjustment for confounders (odds ratio, 0.60; 95% confidence interval, 0.37–0.97; p  = .036). Non‐White, particularly Black/AA and Asian, probands had a trend toward lower rates and numbers of at‐risk family members being seen for counseling/genetic testing. Conclusions: Despite minimizing barriers to genetic testing, non‐White patients were less likely to receive recommended cancer genetics follow‐up, with potential implications for oncologic care, cancer risk reduction, and at‐risk family members. Lay summary: Genetic testing is becoming an important part of cancer care, and we wanted to see if genetics care was different between individuals of different backgrounds. We studied 15, 775 diverse patients with cancer who had genetic testing using a test called MSK‐IMPACT that was covered by research funding. Clinically important genetic findings were high in all groups. However, Black patients were less likely to get recommended counseling compared to White patients. Even after removing many roadblocks, non‐White and especially Black patients were less likely to get recommended genetics care, which may affect their cancer treatments and families. Abstract : Although rates of germline pathogenic variants in cancer predisposition genes varied by self‐reported ancestry, rates in high penetrance genes were similar across all groups, highlighting the importance of genetic testing in cancer patients. Despite minimizing barriers to genetic testing, non‐White, particularly Black, cancer patients were less likely to complete recommended counseling follow‐up compared to non‐Hispanic White patients with potential implications for oncologic care, cancer risk reduction, and at‐risk family members.